Provocative Vocatives in the Gospels: Part 2, Matthew, Luke. Issue 1 (April 2020) - Clark, David J.
This article is the second in a three-part survey of the various vocative forms used in direct discourse in the Gospels, and the similarities and differences among the forms used. Some of the problems associated with finding terms appropriate to each context in English and other languages are raised, and attention is drawn to the complexity of the issues.